A Fuzzy Logic Approach in Modeling and Simulation of a Scheduling System for Hospital Admissions Using ARENA® simulation software - Nurul Atiqah Mat Ayus, Nurul Atiqah (Universiti Teknologi Petronas, 2010)
The aim of this project is to develop a simulation model of a scheduling system based on practical situation implemented on ARENA® simulation software. Besides, this project also seeks to incorporate Fuzzy Logic Control in decision making processes. This project mainly focuses to develop a model of a scheduling system for admission of hospital Emergency Department (ED) using ARENA® simulation software.